`y = cos(1 - 2x)^2` Find the derivative of the function.

Expert Answers
sciencesolve eNotes educator| Certified Educator

You need to evaluate the derivative of the function, hence you need to use the chain rule, differentiating first the cosine, then the power function and then the argument, such that:

`y' = (cos(1-2x)^2)'*((1-2x)^2)'*(1-2x)'`

`y'=(-sin(1-2x)^2)*(2(1-2x))*(-2)`

`y' = (4sin(1-2x)^2)*(1-2x)`

Hence, evaluating the derivative of the function, yields `y' = (4sin(1-2x)^2)*(1-2x).`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question